2006
DOI: 10.1093/jn/136.6.1483
|View full text |Cite
|
Sign up to set email alerts
|

Bioproduction of Conjugated Linoleic Acid by Probiotic Bacteria Occurs In Vitro and In Vivo in Mice

Abstract: Probiotics have been shown to reduce the incidence of colon cancer in animal models. The mechanisms responsible for this activity are poorly defined. Conjugated linoleic acids (CLA) are a group of isomers of linoleic acid (LA) possessing anti-inflammatory and anticarcinogenic properties, which can be produced from LA by certain bacterial strains. In this study, the ability of probiotic bacteria to exert anticarcinogenic effects through the production of CLA was assessed. Incubation of probiotic bacteria (VSL3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(123 citation statements)
references
References 49 publications
5
112
0
2
Order By: Relevance
“…20,21 L. acidophilus was incubated for 18 h at 371C in 10 ml of RPMI-1640 or Mann-Rogosa-Sharpe broth in the presence or absence of 0.5 g/l of linoleic acid suspended in 0.05% Tween-80. Samples were centrifuged at 3500 Â g for 15 min, from which process supernatants were obtained.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…20,21 L. acidophilus was incubated for 18 h at 371C in 10 ml of RPMI-1640 or Mann-Rogosa-Sharpe broth in the presence or absence of 0.5 g/l of linoleic acid suspended in 0.05% Tween-80. Samples were centrifuged at 3500 Â g for 15 min, from which process supernatants were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, b-galactosidase activity was determined using the chemiluminescent substrate AMPGD (3-(4-methoxyspiro[1,2-dioxetane-3,2 0 -tricylo[3.3.1.1]decan]-4-yl)phenyl-b-D-galactopyranoside; Tropix Inc.) as described before. 18,20 Luminescence was induced by the addition of 50 ml 0.2 N NaOH containing 10% Emerald enhancer (Tropix Inc.) and quantitated for 10 s in a luminometer. Increased activity from pIL-8, p2x NF-kB, and pb-actin promoters was calculated by comparing ratios of luciferase to b-galactosidase activities in the cells co-transfected with pIL8-luciferase and pRSV-b-galactosidase, p2x NF-kBluciferase and pRSV-b-galactosidase, or pb-actin-luciferase and pRSV-b-galactosidase, respectively.…”
Section: Transfection and Reporter Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of a mix of bacteria able to form CLA as c9, t11 and t10, c12, called VSL3 was used as probiotic for mice administration [102]. Probiotic was prepared as lyophilized form and mice were fed 30 μL of probiotic (0.03 g VSL3 in 10 ml water) for 3 days.…”
Section: Functional Foods and Probioticsmentioning
confidence: 99%
“…shown that the bacterial cell wall (lipopolysaccharide, lipoteichoicacid, peptidoglycan) and metabolites (such as short chain fatty acid, secreted proteins and so on) of viable lactobacilli play a pivotal role in the maintenance of gastrointestinal immune homeostasis and prevention of inflammation 3,[5][6][7][8] The most common cause of gastroenteritis in people of all ages is enteric caliciviruses (SRSVs) and rotaviruses followed by other enteric viruses like hepatitis A and E virus and human cytomegalovirus (CMV). In developing countries, diarrhea caused by rotavirus in children is often a significant cause of infant morbidity and mortality 3) .…”
Section: Introductionmentioning
confidence: 99%